Geographical distribution of dioecy and its ecological correlates based on fine‐scaled species distribution data from a subtropical island. Issue 1 (2nd December 2019) - Lin, Huan‐Yu; Tseng, Yu‐Hsin; Hsieh, Chang‐Fu; Hu, Jer‐Ming
Abstract: Dioecy is a rather rare sexual expression system guarantees outcrossing to avoid the deleterious effects of inbreeding. The incidence of dioecy varied among local floras and suggested inclining to tropical and oceanic environments, but its eco‐correlates received little research attention. In this article, we explored geographical patterns and variations in sexual expression systems of angiosperms in mountainous environments of Taiwan, a subtropical island in East Asia. A comprehensive geo‐database of vegetation inventories and herbarium specimens were used to identify eco‐correlates causing variations in the horizontal geographical extent and along a large elevational gradient of more than 3, 500 m. We found the average incidence of dioecy in the flora of Taiwan to be 8.2%, but it exhibits geographical variations from islets in the Taiwan Strait to the Pacific Ocean. Detailed studies on the main island of Taiwan revealed that the incidence of dioecy varied among land cover types and elevational zones. An apparent two‐step decreasing pattern of dioecy percentages with elevation was found, with the highest proportion in the lowlands (0–600 m; 23.96%), followed by middle elevations (600–2, 700 m; 20.87%) and subalpine regions (2, 700–3, 900 m; with a range of 11.38–0%). We found that spatial variations of dioecy were associated with eco‐correlates of land cover, elevation, woodiness, species richness, and mean annual temperature. Results of this study partially support Bawa's hypothesis of a higher incidence of dioecy on oceanic islands, and is consistent with Baker and Cox's observations of richer dioecious species on high‐mountain islands in the tropics and subtropics. Abstract : Dioecy is a rather rare breeding system in plants that guarantees outcrossing to avoid the deleterious effects of inbreeding. Tropics and oceanic islands were speculated as being hotspots of dioecy, but its presence can vary among local floras. This article not only identified a continental‐oceanic variation of dioecy, but revealed an apparent two‐step decreasing pattern along altitude based on numerous investigation data in East Asia.